"Fighting Mr. Sleepy": A Metaphor for Black Graduate Student Experiences. Issue 14 (6th December 2021) - Austin, Jasmine T.
ABSTRACT: While reflecting on early morning conversations with my dad, I became aware of how he influences my ontoepistemological approach to studying the Black graduate student experience. In this essay, I narrate my defining moment as I began asking my research participants modified versions of the questions my dad asks me. It is through these reflections that I realize, my dad may not have been asking me questions, instead, making observations. Powerful ones of perseverance. Subsequently, I encourage health communication scholars, practitioners, faculty, staff, and peers to embrace an active role as counter agents to the psychological stress and fatigue of Mr. Sleepy.